Lecturer Talks: Classroom Interaction’s Identifying - Yunda Lestari (International Journal of Language Teaching and Education, 2017)
This study aimed to find out what category of lecturer talks applied by lecturers in classroom interaction. This study was a descriptive survey. The participants were chosen by using purposive sampling technique where there were four English lecturers who taught at Second Semester Class of English Department of Baturaja University in the academic year of 2016/2017. The data were taken through observation, questionnaire and interview. Camera recorder and checklist were the instruments used in this study. The data were identified by using FLINT (Foreign Language Interaction) system as developed by Moskowitz (1971). The result of the study showed that the total of frequencies the deals with feeling were 9 or 1.6%, praises or encourages were 57 or 9.9%, uses ideas of students were 42 or 7.3%, asks questions were 199 or 34.6%, gives information were 92 or 16%, gives directions were 151 or 26.3% and criticizes student behavior were 25 or 4.3%. In conclusion, the category of lecturer applied by lecturers was asks questions in classroom interaction that the best ways to develop their role as an initiator and strategies that promote interaction in classroom activity. Keywords: Classroom Interaction, Lecturer Talks, FLINT